A rare case of Zinner syndrome with unilateral testicular agenesis and aberrant course of left common iliac artery - Dixit Varma; Ibrahim Khalil Ullah; Madhurjya Kumar Thakur (The Egyptian Journal of Radiology and Nuclear Medicine, 2023)
Abstract Background Zinner syndrome is a rare Wolffian duct anomaly presenting as a triad of unilateral renal agenesis, ipsilateral seminal vesicle cyst and ipsilateral ejaculatory duct obstruction. The condition is due to a developmental anomaly leading to malformation of the mesonephric duct. Magnetic resonance imaging is considered to be the gold standard for the diagnosis of Zinner syndrome. Due to the limited number of cases reported in the literature, the associations of Zinner syndrome are not well established. Case presentation In this case report, we are presenting a case of a 38-year-old male with dysuria, intermittent pain in the scrotum and lower abdomen and painful ejaculation for the past six months. Imaging findings led to the diagnosis of Zinner syndrome, with unilateral testicular agenesis and an aberrant course of the left common iliac artery. Conclusions Apart from the known associations of Zinner syndrome, testicular agenesis in a patient with Zinner syndrome has not been reported in the literature and is an important addition to the limited literature available.